Pembelajaran Organisasi di Rumah Sakit Umum Daerah - Yoberth Kornelius (Journal on Education, 2023)
This study aims to identify and describe organizational learning in the Regional General Hospital of Central Sulawesi Province. The population of this study was employees (including health workers) from two Regional General Hospitals in Central Sulawesi Province with class B status with a total of 1,478 employees, while the study sample consisted of 265 respondents. Data collection techniques consist of observation and questionnaires. Quantitative data analysis using descriptive statistics. The results showed the dimension with the highest cumulative mean value was knowledge transfer and integration, while the lowest was system perspective. Based on these results, the problem of organizational learning, especially in the system perspective, therefore that this can be improved, especially the use of the system as a whole. The Hospital to provide direction and training to its employees to utilize the existing system.